Random Fixed Point Theorems and Applications to Random First-Order Vector-Valued Differential Equations. (5th March 2021) - El-Ghabi, Adil; Khchine, Abdelmjid; Taoudi, Mohamed Aziz
Abstract : In this paper, we establish several random fixed point theorems for random operators satisfying some iterative condition w.r.t. a measure of noncompactness. We also discuss the case of monotone random operators in ordered Banach spaces. Our results extend several earlier works, including Itoh's random fixed point theorem. As an application, we discuss the existence of random solutions to a class of random first-order vector-valued ordinary differential equations with lack of compactness.